Incidence of hyponatremia with vasopressin exposure in critically ill pediatric patients for postoperative cardiac support and shock management: A single-center, retrospective, case–control study - Gustavo R. Alvira-Arill; Nian S. Chang; Helen Y. Lee; Nicole Tomas; Sharmeen Y. Roy; Balagangadhar R. Totapally (Journal of Pediatric Critical Care)
Background: Vasopressin is used adjunctively to catecholamines for cardiovascular support but may be associated with hyponatremia. The objective of this study was to investigate the incidence of hyponatremia in critically ill pediatric patients receiving vasopressin for postoperative cardiac support or vasodilatory shock. Subjects and Methods: A retrospective and case–control study of pediatric patients who received vasopressin for postoperative cardiac support or vasodilatory shock at a free-standing, pediatric hospital during a 4-year period was performed. The cases were defined by the development of hyponatremia (serum sodium level <130 mmol/L) during vasopressin exposure. Differences in characteristics associated with hyponatremia were assessed through the generalized linear models with binomial distribution. Results: In this study, 134 patients who received vasopressin for postoperative cardiac support or shock management were assessed and 28 (21%) patients developed hyponatremia during exposure. Most patients assessed were neonates (90/134 [67.2%]) and received vasopressin for postoperative cardiac support (86/134 [64.2%]). Multivariable analysis identified two factors independently associated with hyponatremia: longer duration of vasopressin infusion (aOR [95% CI]: 1.03 [1.02–1.05]; P ≤ 0.05) and lower serum sodium before exposure (aOR [95% CI]: 0.86 [0.79–0.93]; P ≤ 0.05). Vasopressin exposure of at least 2 days was found to be associated with higher hyponatremia incidence (uOR [95% CI]: 14.67 [5.67–42.24]; P ≤ 0.05). Conclusions: This study demonstrated the high incidence of hyponatremia during vasopressin exposure in pediatric patients managed for postoperative cardiac support or vasodilatory shock. Longer duration of vasopressin exposure and lower serum sodium before exposure were independently associated with hyponatremia.